PREVALENCE OF SEXUALLY TRANSMITTED INFECTIONS AND SEXUAL RISK BEHAVIOR AMONG FEMALE SEX WORKERS IN NINE PROVINCES IN INDONESIA, 2005 - TANUDYAYA, Flora K; RAHARDJO, Eko; KEMMY AMPERA PURNAMAWATI; SEDYANINGSIH MAMAHIT, Endang R; BOLLEN, Liesbeth Jm; MADJID, Nurholis; FAHMI DAILI, Sjaiful; PRIOHUTOMO, Sigit; MORINEAU, Guy; NURJANNAH; ROSELINDA; ANARTATI, Atiek S (Southeast Asian journal of tropical medicine and public health, 2010)
The objective of this study was to assess the sexually transmitted infection (STI) prevalence and sexual risk behavior among female sex workers (FSWs) in Indonesia. This cross-sectional 2005 study involved 2500 FSWs in nine provinces in Indonesia. Informed consent was obtained; behavioral and clinical data were collected. Specimens were collected for STI testing, endocervical swabs were tested for Chlamydia trachomatis and Neisseria gonorrhoeae (PCR), vaginal smears were cultured to detect Trichomonas vaginalis and sera were tested for syphilis (RPR and TPHA). The prevalence of chlamydial infection was 43.5%, gonorrhea 28.6%, trichomoniasis 15.1%, and syphilis 8.7%; the prevalence of any STI was 64.0%. Inconsistent condom use, younger age, and higher number of clients were independent risk factors for the presence of gonorrhea/chlamydia. Inconsistent condom use was common (73.2%); starting sex work at younger age, and higher number of clients were independent risk factors. Vaginal douching was reported by 89.6% of FSWs; no association with gonorrhea/chlamydial infection was found. This study identified a high STI prevalence and low consistent condom use among FSWs in Indonesia. This will need to be addressed to prevent further spread of infections, including HIV.